Investigating the Impact of the Non-Structural Proteins of Respiratory Syncytial Virus on the Type I Interferon Response - Efstathiou, Claudia Mary (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2023)
Respiratory syncytial virus is the leading cause of bronchiolitis in infants, causing 33.2 million hospital admissions and over 118,000 deaths each year. The primary site of RSV infection are the epithelial cells of the respiratory tract. On infection RSV evades the immune response through several mechanisms, including subversion of responses to the anti-viral cytokine IFNα by interacting with the JAK-STAT pathway. IFNα is a potent antiviral cytokine that quickly causes an up-regulation in over 500 IFN stimulated genes to make the cell less permissive to infection and viral growth. The action of RSV prevents the up-regulation of ISGs, including MxA, ISG15, USP18 and PKR, which prevents infected cells from mounting a robust anti-viral response. Our research focuses on the immune evasive role of RSV?s two non-structural proteins, NS1 and NS2, and the mechanism by which they limit JAK-STAT signalling. We expressed NS1 and NS2 in human alveolar epithelial cells (A549) and bronchial epithelial cells (BEAS 2b) and analysed their effect upon the JAK-STAT pathway. We discovered that expressing NS1 in A549 and BEAS 2b cells lead to a significant reduction in ISGs, while NS2 had no significant effect. There was no matched reduction in pSTAT1 or pSTAT2 in either cell line. However, BEAS 2b had increased STAT1 and STAT2 phosphorylation with NS1 expression. By studying the subcellular localization of STAT1 we have shown that expression of NS1 reduced STAT1 trafficking to the nucleus, and altered STAT2 localization, providing a new mechanism by which RSV NS1 prevents efficient JAK-STAT signalling. While the primary site of RSV infection is epithelial cells of the upper respiratory track, there is some evidence that immune cells can be infected by RSV. To examine the extent of the permissiveness of circulating immune cells, adult PBMCs were incubated with RSV and the resulting infection measured. We found that around 2% of lymphocytes became infected and that there was a reduction in IFNα sensitivity after RSV infection. This reduction in responsiveness to IFNα may result in delayed viral clearance and altered phenotypic differentiation. Taken together, this work has shown that RSV NS proteins have key immune evasion roles that are used to overcome the IFNα response by reducing the signalling through the JAK-STAT pathway. The ability of RSV NS proteins to limit the activity of IFNα identifies the NS proteins as targets for therapeutic treatments for RSV. Our work gives a better understanding of how RSV NS proteins acts to subvert the immune response in the most clinically relevant cell types.
APPROVED
Keywords: Respiratory Syncytial Virus; JAK/STAT; Signalling; Virology; Immunology